The Soviet Union's position on the Angolan civil war and its impact on sustainable development on the continent (Journal of the College of Basic Education, 2026)
History is a mirror to peoples, a means of understanding the present and anticipating the future. It is not limited to recounting events, but extends to analyzing facts and revealing their profound impact on the trajectories of human and social development. From this perspective, the topic of the Soviet Union's position on the Angolan Civil War (1967-1974) gains special significance, as it represents a clear example of the intertwining of political, ideological, and international dimensions in the history of developing countries, amidst the Cold War conflict that prevailed at the time.Studying this historical event is not limited to understanding the course of the war alone, but extends to analyzing the positions of the major powers and their impact on the path of development and stability in newly independent African countries. In this context, the research topic intersects with the conference theme: "Modern Trends in the Humanities, Education, and Psychology in Sustainable Development," in that it highlights the importance of the historical dimension as a fundamental resource for understanding the complexities of the present and provides lessons learned that can be employed in building sustainable development policies based on an awareness of history and people's experiences. History, with its facts and implications, is inseparable from the trajectories of human and social development. Civil wars and international conflicts are among the factors that hinder countries' stability and limit their opportunities for achieving sustainable development. Hence, the importance of recalling history in light of modern trends in the humanities, as a means of understanding roots, addressing crises, and formulating development strategies that avoid repeating the tragedies of the past